2000
DOI: 10.1159/000017237
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Endothelial Dysfunction in Patients with Alzheimer’s Disease

Abstract: In view of accumulating evidence of vascular pathology in Alzheimer’s disease (AD), we tested the hypothesis that AD patients have impaired endothelial function. This was assessed using the technique of strain-gauge venous occlusion plethysmography, which measures forearm blood flow (FBF). Intra-arterial (brachial) infusion of acetylcholine (ACh) and sodium nitroprusside (SNP) was used to assess local endothelial dependent and independent responses, respectively. There was no difference in the basal FBF of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Although several studies have investigated a relationship between vascular tone regulation and AD, the published results are inconsistent. 7 13 Dede et al 7 evaluated endothelial function in patients with AD and reported significantly lower FMD values in patients with AD compared to normal controls, which is consistent with our findings. Dede and colleagues found endothelial dysfunction in patients with AD who did not have vascular risk factors or diseases.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although several studies have investigated a relationship between vascular tone regulation and AD, the published results are inconsistent. 7 13 Dede et al 7 evaluated endothelial function in patients with AD and reported significantly lower FMD values in patients with AD compared to normal controls, which is consistent with our findings. Dede and colleagues found endothelial dysfunction in patients with AD who did not have vascular risk factors or diseases.…”
Section: Discussionsupporting
confidence: 91%
“…3 6 Although these findings suggest that vascular factors are associated with AD pathogenesis, results regarding vascular functioning (eg, endothelial functioning or arterial stiffness) remain inconsistent. Some authors 7 10 have reported vascular dysfunction in AD or vascular function differences between these two dementia groups; however, others 11 13 have shown neither vascular dysfunction in AD nor differences between the 2 dementia groups. These inconsistent results may be partly due to the use of different measures to assess vascular function.…”
Section: Introductionmentioning
confidence: 99%
“…Determining endothelial function from peripheral arteries can reflect vascular endothelium in the brain. This was proved in an experimental study showing that cerebral vessels respond like peripheral vessels to acetylcholine infusion 35 …”
Section: Discussionmentioning
confidence: 88%
“…This finding also indicates that endothelial dysfunction may occur in AD, although studies on this are limited. One study evaluated endothelial function of 17 patients with AD using venous occlusion plethismography and found no difference from normal controls 35 . Serum soluble intercellular adhesion molecule‐1, soluble E‐selectin, and thrombomodulin were evaluated as potential markers for endothelial dysfunction in different studies, and significantly greater levels were detected in subjects with AD 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to many positive reports about this strong relationship, others question its relevance, considering IR as necessary but not sufficient to induce ED [ 317 ]. Indeed, a study in Alzheimer patients, who are IR, failed to demonstrate ED [ 264 ]. Also a study in 60‐year‐old subjects, many of which have at least age‐related IR, did not reveal ED [ 435 ].…”
Section: Microcirculation In States Of Metabolic Syndromementioning
confidence: 99%